2007
DOI: 10.1016/j.ccr.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Chemotaxis as a Mechanism of Tumor Cell Homing to Lymphatics via Interstitial Flow and Autocrine CCR7 Signaling

Abstract: CCR7 is implicated in lymph node metastasis of cancer, but its role is obscure. We report a mechanism explaining how interstitial flow caused by lymphatic drainage directs tumor cell migration by autocrine CCR7 signaling. Under static conditions, lymphatic endothelium induced CCR7-dependent chemotaxis of tumor cells through 3D matrices. However, interstitial flow induced strong increases in tumor cell migration that were also CCR7 dependent, but lymphatic independent. This autologous chemotaxis correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
490
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 495 publications
(512 citation statements)
references
References 46 publications
17
490
3
2
Order By: Relevance
“…In addition to activating lymphatic endothelium, lymphatic drainage also facilitates interstitial flow, directed towards the lymphatics. This directional flow promotes cell homing by biasing pericellular autocrine chemokine gradients thereby driving DC and tumor cell chemotaxis towards draining lymphatics [42,43]. Thus, lymphatics are dynamic sensors of acute biomechanical changes that accompany the onset of tissue injury and inflammation and are inherently coupled to immune cell trafficking and antigen transport to and within the draining LN [44].…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to activating lymphatic endothelium, lymphatic drainage also facilitates interstitial flow, directed towards the lymphatics. This directional flow promotes cell homing by biasing pericellular autocrine chemokine gradients thereby driving DC and tumor cell chemotaxis towards draining lymphatics [42,43]. Thus, lymphatics are dynamic sensors of acute biomechanical changes that accompany the onset of tissue injury and inflammation and are inherently coupled to immune cell trafficking and antigen transport to and within the draining LN [44].…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…Furthermore, some tumor cells also express VEGFR-3 and thus may benefit from autocrine signaling of VEGF-C or -D [121,[125][126][127][128][129]. Such autocrine signaling could help tumor cells home to lymphatics by guiding them in the direction of flow [42]. Finally, in addition to driving lymphangiogenesis, tumor VEGF-C also upregulates the expression of CCL21 by lymphatic endothelium to further promote lymphatic invasion via CCR7 expression [121].…”
Section: Chronic Graft Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the resulting gradient is small, chemokine sensing is known to be extremely sensitive such that even a 1% to 2% concentration difference across a cell can drive chemotaxis. Indeed, recent studies have shown that interstitial fluid flow alone can drive CCR7-dependent chemotaxis in CCL21 þ tumor cells, and that this autocrine gradient synergizes with the steep local paracrine gradient from a CCL21 þ lymphatic vessel (34). This "autologous chemotaxis" can also occur with other chemokine-receptor autocrine loops, for example as shown in CXCR4-dependent flow-driven invasion of glioma cells, which also express its ligand CXCL12 (35).…”
Section: Lymphatic Transport Of Cellsmentioning
confidence: 99%
“…The cells might directly sense the surface forces induced by flow, the drag and tethering forces that result from these surface forces on the ECM, or the effects may be more indirect. For example, recent work has shown that IF can alter the extracellular distribution of secreted chemokines or morphogens and thus direct cell migration or capillary morphogenesis (Helm et al, 2005;Fleury et al, 2006;Shields et al, 2007). Flow may also be focused on small portions of a porous space by larger tissue structures and have a strong effect on cells embedded in that space (Tada and Tarbell, 2000).…”
Section: Introductionmentioning
confidence: 99%